An External Communication Audit of Trinity Fellowship Discipleship Ministry - Gatobu, Sospeter Kaai. (Daystar University, School of Communication., 1996)
The purpose of this study was to perform an external communication audit of Trinity Fellowship Discipleship Ministry's key publics, so as to recommend an effective communication strategy for the organization. The research methods employed were: mail survey using self administered questionnaires; interviews among the staff members of Trinity Fellowship Disciple- ship Ministry and document analysis. This study found that although the respondents' attitude towards the organization was positive, their level of involvement was low. The majority (70%) preferred to pray for the organization. This study also found out that the organization's overall goal seems to have shifted from serving teachers and student teachers at the university to serving everyone else on the mailing list. This was confounded by lack of clear communicating policy in line with the organization's goal and objectives. Consequently, the flow of information to and from the organization was not effective.
Thesis
Keywords: external communication audit; effective communication strategy